Periodontal microsurgery: A leap in surgical intervention - Surinder Sachdeva; Jyotsna Goyal; Ritika Jaiswal; Sanjeet Gill; Swantika Chaudhry; Deepak Kochar (Wolters Kluwer Medknow Publications, 2015)
Recent developments in medical and dental field have shown that magnification and microsurgery can greatly improve clinical practice. The main aim of surgical intervention is not only the survival of the patient or one of his organs but also the effort to preserve a maximum amount of function and to improve patient comfort. These demands are mostly met owing to a minimally invasive surgical approach. The improved visual acuity provided by magnification opens a whole new world for those who make effort and take time to become proficient in microsurgical principles and procedures. The promising periodontal microsurgery will provide new possibilities to improve the therapeutic results for variety of periodontal surgeries. The purpose of this paper is to provide a brief review of periodontal microsurgery, role of magnification systems, and advantages of microsurgery over conventional surgery.